2001
DOI: 10.1037/0735-7028.32.5.537
|View full text |Cite
|
Sign up to set email alerts
|

Work activities of academic clinical psychologists: Do they practice what they teach?

Abstract: Do PhD-level clinical psychologists who work in academic settings engage in both research and clinical practice, as the Boulder model recommends? Clinical psychology faculty members in 3 types of psychology departments were surveyed regarding their actual and preferred work activities and their attitudes toward clinical practice. Respondents indicated that they spent more than twice as much time in research as in clinical activity, with many (44%) reporting no involvement in clinical practice. Implications of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 11 publications
3
32
1
Order By: Relevance
“…This is consistent with the literature that has described the desire of new faculty to enhance their own clinical skills and, if possible and applicable, also work toward a level of counseling licensure within their states (DiLillo et al, 2006;Himelein & Putnam, 2001). The current research also identified some significant themes related to how pre-tenured counselor educators view or experience DCS which include: feeling significant restrictions on time to be able to pursue DCS; lack of departmental or institutional support to pursue DCS; little value placed on DCS within tenure processes; the idea that skill and practice remain current as a result of a DCS connection; the sense that DCS lends credibility to both teaching and research endeavors; and feeling that DCS plays an important role in the evolving identity of counselor educators who are new in their faculty careers.…”
Section: Qualitative Analysissupporting
confidence: 79%
See 3 more Smart Citations
“…This is consistent with the literature that has described the desire of new faculty to enhance their own clinical skills and, if possible and applicable, also work toward a level of counseling licensure within their states (DiLillo et al, 2006;Himelein & Putnam, 2001). The current research also identified some significant themes related to how pre-tenured counselor educators view or experience DCS which include: feeling significant restrictions on time to be able to pursue DCS; lack of departmental or institutional support to pursue DCS; little value placed on DCS within tenure processes; the idea that skill and practice remain current as a result of a DCS connection; the sense that DCS lends credibility to both teaching and research endeavors; and feeling that DCS plays an important role in the evolving identity of counselor educators who are new in their faculty careers.…”
Section: Qualitative Analysissupporting
confidence: 79%
“…The journey toward tenure can be challenging and complex (Austin & Rice, 1998;Cohen et al, 2003;Himelein & Putnam, 2001), and the existing research indicates that new counselor educators are often expected to "hit the ground running" (Magnuson et al, 2001). New faculty are also faced with figuring out the roles that they are required to serve in academic settings, in addition to navigating the tenure and renewal processes within their institutions.…”
Section: Implications and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cumulative effect these challenges may contribute to recent fi gures indicating that 44% of applied academic psychologists are uninvolved in any type of clinical practice (Himelein & Putnam, 2001). One major hurdle is the requirement of postdoctoral supervised experience, which ranges from 0 to 4,000 hr, depending on the state in which one wishes to become licensed.…”
Section: Pursuing Applied Interestsmentioning
confidence: 99%